2009
DOI: 10.1080/13803390902780201
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging sequential-finger movement activation differentiating good and poor writers

Abstract: Good and poor fifth-grade writers differed, after controlling for multiple comparisons, in 42 brain regions on group maps and then individual brain analyses for fMRI contrast between tapping adjacent fingers sequentially and same finger repeatedly. Of these, 11 regions were correlated with both handwriting and spelling (transcription). Gender differences on the fMRI contrast, with girls more activated, occurred only in left superior parietal, which was correlated with handwriting and spelling. Significance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…Also of interest, several of these learning activities involving ordering words in sentences or other syntax units were also related to spelling outcomes, consistent with sequencing of elements being related to spelling (Richards et al, 2009) and value of teaching to both the word and syntax levels of language in the same lessons.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Also of interest, several of these learning activities involving ordering words in sentences or other syntax units were also related to spelling outcomes, consistent with sequencing of elements being related to spelling (Richards et al, 2009) and value of teaching to both the word and syntax levels of language in the same lessons.…”
Section: Resultsmentioning
confidence: 67%
“…However, the nature of the user-computer interface may be different for typically developing writers and those with SLDs affecting writing in upper elementary and middle school. For example, students with dysgraphia (Richards, Berninger, Stock, Altemeier, Trivedi, & Maravilla, 2009) have been shown to have specific difficulty in sequential finger movements, which are needed for writing with pen and paper and keyboard.…”
Section: Introductionmentioning
confidence: 99%
“…These findings provide converging validation of brain-behavior relationships between left fusiform and orthographic coding during middle childhood. Both behavioral measures, which have been shown in prior research to explain unique variance in handwriting and composing skills (e.g., Abbott & Berninger, 1993), participate in the orthographic loop that integrates internal written word representations with writing their constituent letters via the hand (and sequential finger movements) in the external environment (see Berninger et al, 2006;Berninger, Raskind, Richards, Abbott, & Stock, 2008;Richards et al, 2009b). Thus, the final hypothesis tested examined whether this brain-behavior relationship between left fusiform and expressive orthographic coding might be relevant for higher-order composing.…”
Section: Writing Highly Practiced Letters Automaticallymentioning
confidence: 99%
“…In the next step, for these exact clusters, the individual z-scores were averaged for each individual after the brain was co-registered to the standard brain. We have used individual brain analyses in the past to compute correlations for the purpose of identifying and validating brain-behavior relationships in writing (e.g., Richards, Berninger, & Fayol, 2009a;Richards, Berninger, Stock, Altemeier, Trivedi, & Maravilla, 2009b).…”
Section: Poor Writersmentioning
confidence: 99%
“…Compared with men, women are thought to be better writers; however fMRI does not show significant differences in brain activation for either sex while writing. 9 The same study found significant differences between good and poor writers while handwriting, mostly in brain regions involved with planning for serial finger movements. The opposite of writer's block is also known to occur, and it can be temporary or affect an individual all of his or her life.…”
mentioning
confidence: 83%